2015
DOI: 10.1016/j.cell.2015.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory TNFα Impairs Memory via Astrocyte Signaling

Abstract: The occurrence of cognitive disturbances upon CNS inflammation or infection has been correlated with increased levels of the cytokine tumor necrosis factor-α (TNFα). To date, however, no specific mechanism via which this cytokine could alter cognitive circuits has been demonstrated. Here, we show that local increase of TNFα in the hippocampal dentate gyrus activates astrocyte TNF receptor type 1 (TNFR1), which in turn triggers an astrocyte-neuron signaling cascade that results in persistent functional modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
247
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(257 citation statements)
references
References 51 publications
6
247
1
3
Order By: Relevance
“…Intraperitoneal LPS typically induces about half of its systemic (and brain) cytokine response through C5a receptors with the other half is through toll-like receptor 4 (TLR-4). While others showed that pro-inflammatory cytokines are acting through glial cells to perturb neuron homeostasis, 27 our ex vivo results demonstrated that the loss of CAR in neurons can be via a direct effect of TNF and IFN-g. It will be critical to determine whether TNF or IFN-g play a role in the reduction of CAR levels in the DG.…”
Section: Inflammation-induced Car Losscontrasting
confidence: 46%
“…Intraperitoneal LPS typically induces about half of its systemic (and brain) cytokine response through C5a receptors with the other half is through toll-like receptor 4 (TLR-4). While others showed that pro-inflammatory cytokines are acting through glial cells to perturb neuron homeostasis, 27 our ex vivo results demonstrated that the loss of CAR in neurons can be via a direct effect of TNF and IFN-g. It will be critical to determine whether TNF or IFN-g play a role in the reduction of CAR levels in the DG.…”
Section: Inflammation-induced Car Losscontrasting
confidence: 46%
“…In addition, hippocampal AAV-TNF mice exhibited a decrease in contextual fear expression relative to acquisition, consistent with inhibition of consolidation and/or recall of contextual memory. Interestingly, a similar deficit in contextual fear memory was observed in a mouse model of experimental autoimmune encephalomyelitis (EAE): the deficit co-occurred with a moderate increase in hippocampal TNF and was mediated by the TNF receptor 1 expressed on astrocytes (Habbas et al, 2015). Further evidence that increased hippocampal TNF increases sensitivity to aversive stimuli was obtained in the twoway avoid-escape test: as for ICV AAV-TNF mice, mice expressing increased hippocampal TNF exhibited increased freezing together with decreased compartmental transfers; these changes suggest increased anxiety and, therefore, that TNF increases the approachavoidance conflict and resultant behavioral inhibition that has been attributed to ventral hippocampus in such ambivalent environments (Bannerman et al, 2014;McNaughton and Gray, 2000).…”
Section: Effects Of Hippocampal Tnfmentioning
confidence: 71%
“…Experimental autoimmune encephalomyelitis (EAE) in mice, a model of multiple sclerosis, led to reduced activity in the center of an open field and impaired learning-memory, concurrent with increased brain TNF levels and signaling; certain of these effects were blocked by i.c.v. etanercept (Acharjee et al, 2013;Haji et al, 2012;Habbas et al, 2015). Chronic psychosocial stress in mice has also been demonstrated to increase TNF and interleukin levels and to lead to depression-and anxiety disorder-relevant behavior (Azzinnari et al, 2014;Fuertig et al, 2016;Kinsey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines, autoantibodies and complement factors have all been shown to alter neuronal activity, either directly, by modulating the production of glutamate by microglia, or, in the case of TNF, by enhancing neuronal activity via activation of TNF receptors on astrocytes (Habbas et al, 2015;Piani et al, 1991) …”
Section: Discussionmentioning
confidence: 99%